0159 Reduced REM Sleep Percent in Frequent Cannabis Versus Non-Cannabis Users. (27th May 2020) - Carr, M; Borcsok, R; Taylor, M; Segust, S; Pigeon, W; Bradshaw, C
Abstract: Introduction: THC (the main psychoactive component of cannabis) has been shown to suppress REM sleep and decrease sleep latency, although this is not consistently replicated. Increased dream vividness is reported to occur in abstinent cannabis users, although dream quality in active users is unstudied. The current study aimed to assess the effects of cannabis use compared to non-use on objective sleep measures, dream reports, and self-reported anxiety, memory, and sleep quality. To collect objective sleep data we piloted the use of a portable PSG headband that allows EEG and EOG recording at home. Methods: 12 regular cannabis users (> 3 days per week) & 9 non-users (aged 19 - 27; 43% female) participated; participants used no other drugs or alcohol on study nights. The most common form of cannabis use was smoking in joints with tobacco (range = 1 - 15 per day). Participants wore the PSG headband (the Hypnodyne ZMax) over 2 nights at home (2 nd night used for analysis), and were instructed to awaken 4 times across the night to fill out brief dream reports. Objective sleep measures included TST, Sleep latency, REM latency, and REM percent. Self-report measures included the Pittsburgh Sleep Quality Index, Everyday Memory Questionnaire, and State-Trait Anxiety Index. Dream measures included recall frequency, word length, and three attributes rated on a 1–7 Likert scale - sensory vividness, emotional intensity, and bizarreness. Results: There were no group differences on self-report measures. Cannabis users showed longer REM latency (t=2.23, p=.04) and lower REM% (U=22, p=.02); there were no other objective group differences. Cannabis users reported higher bizarreness in their dreams (t=2.07, p=.05); there were no other dream differences. Conclusion: The study presents a novel approach to assess sleep at home and cannabis use. Significant differences emerged between users and non-users on REM latency, REM%, and dream bizarreness. Support: N/A